Complementing muscle regeneration—fibro-adipogenic progenitor and macrophage-mediated repair of elderly human skeletal muscle - Jonas Brorson; Lin Lin; Jakob Wang; Amanda Bæk; Tine Borum Billeskov; Frederik Forsberg Thybo; Jesper Just; János Haskó; Christen Ravn; Rehne L. Hansen; Mats Bue; Jens Otto Lunde Jørgensen; et al. (Nature Communications)
Abstract The capacity to regenerate skeletal muscle after injury requires a complex and well-coordinated cellular response, which is challenged in aged skeletal muscle. Here, we unravel the intricate dynamics of elderly human skeletal muscle regeneration by combining spatial, temporal, and single cell transcriptomics. Using spatial RNA sequencing (n = 3), we profile the expression of human protein-coding genes in elderly human skeletal muscle biopsies before as well as 2-, 8-, and 30-day post injury (NCT03754842). Single Cell-Spatial deconvolution analysis highlights monocytes/macrophages and fibro-adipogenic progenitors (FAPs) as pivotal players in human muscle regeneration. By utilizing flow cytometry (n = 9) and cell sorting we confirm the increased cellular content and activity during regeneration. Spatial correlation analysis unveils FAPs and monocytes/macrophages co-localization and intercellular communication, mediated by complement factor C3. Immunostaining confirms C3 expression in FAPs and FAP secretion of C3, suggesting a role in phagocytosis of necrotic muscle cells. Finally, functional assays demonstrate C3’s impact on human monocyte metabolism, survival and phagocytosis, unveiling its involvement in skeletal muscle regeneration. These insights elucidate the FAP-macrophage interplay in aged human muscle with perspectives for future therapeutic interventions to reduce the age-induced decline in regenerative capacity.